ANÁLISE DO CONFORTO TÉRMICO EM CONTEINER EM CURITIBA/PR - Campanharo, Maressa; Rossi, Francine Aidie (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
In the search for new materials to reduce environmental impacts in construction, architects and engineers have used the containers for residential, commercial and service use. Considering that the container is a metallic box made of Corten steel, thermal and acoustic insulation is of extreme importance to the comfort of the users. The use of simulation programs anticipates conflicts and problems regarding thermal performance. The goal of this work is to analyze the thermal comfort of a container located in Curitiba/PR, considering two different situations, one without insulation e one with insulation. In general, the insulation tested helped to increase the thermal comfort in all season, with except the summer. For the winter the insulation was not sufficient to ensure comfort regarding the window faced south. In this situation, the cold discomfort could be explained by the window orientation, because there is little incidence of solar radiation in this façade.